2020
DOI: 10.1039/c9ra05878h
|View full text |Cite
|
Sign up to set email alerts
|

Seven new metabolites of drostanolone heptanoate by using Beauveria bassiana, and Macrophomina phaseolina cell suspension cultures

Abstract: Incubation of drostanolone heptanoate (1) with B. bassiana and M. phaseolina afforded seven new and two known metabolites.The main sites of hydroxylation include C-5, C-7, C-11, C-14, C-15, and C-20, hydrolysis at C-17, and reduction at C-3 of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…19,20 There are several studies on metabolism of methasterone (1) has been reported. 10,18,21,22 In our continuing studies of biotransformation on steroids, [23][24][25][26][27][28][29][30][31] previously biocatalysis of methasterone (1) was performed by our research group, which resulted into several new anti-inammatory compounds. 32 Based on the previous results of compound 1, biotransformation of 1 was performed again by using Macrophomina phaseolina and Cunninghamella blakesleeana, which have been demonstrated to be effective cell cultures for bioconversion of steroids.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 There are several studies on metabolism of methasterone (1) has been reported. 10,18,21,22 In our continuing studies of biotransformation on steroids, [23][24][25][26][27][28][29][30][31] previously biocatalysis of methasterone (1) was performed by our research group, which resulted into several new anti-inammatory compounds. 32 Based on the previous results of compound 1, biotransformation of 1 was performed again by using Macrophomina phaseolina and Cunninghamella blakesleeana, which have been demonstrated to be effective cell cultures for bioconversion of steroids.…”
Section: Introductionmentioning
confidence: 99%